Access, Acquisition and Utilisation of Basic Literacy Education as Determinants of Life-Improvement Skills of Rural Adult Learners in Oyo and Ondo States, Nigeria (2012)
The need to expand adult learning programmes for individual in order to function has made the issues of access, acquisition and utilisation of basic literacy education germane in developing countries. Nigeria has been involved in various basic educational activities aimed at increasing access to literacy education for the enhancement of learners‘ daily living by establishing State Agencies for Adult and Non-Formal Education. However, there is a dearth of empirical studies that show the extent to which the expanded access to basic literacy education has influenced life improvement skills of the beneficiaries. This study, therefore, examined the influence of access, acquisition, and utilisation of basic literacy education on life-improvement skills of rural adult learners in Oyo and Ondo states, Nigeria. Survey research design of ex-post facto type was adopted. A total of 1,310 adult learners (Oyo: 579, Ondo: 731) were selected through stratified and simple random sampling techniques. Literacy Access Questionnaire (r = 0.81), Literacy Acquisition Questionnaire (r = 0.79), Literacy Utilisation Questionnaire (r = 0.75) and Life-improvement Skills Scale (r = 0.84) were used for data collection. These were complimented with six sessions of Focus Group Discussion (FGDs) with adult learners. Five research questions were answered and three hypotheses tested at 0.05 level of significance. Data were analysed using percentage, t-test, Multiple regression and context analysis. Access was expanded by annual average of 15.04% and 35.07% in Oyo and Ondo states respectively. The existing curriculum met the life-improvement skills need of more than 80.0% of the beneficiaries. Significant relationship existed among acquisition and utilisation of basic literacy skills and life-improvement skills of beneficiaries (R=0.24, p < 0.01). The linear combination of access, acquisition and utilisation of basic literacy skills was significant (F (3, 1306 =351.525, p < 0.05) and contributed 42.17% to the variance of dependent measures. Access, acquisition and utilisation of basic literacy skills influenced life-improvement skills as follows: family and home management skills (β = 0.41; p < 0.05), health/hygiene management skills (β = 0.34; p < 0.05), income generation skills (β = 0.30; p < 0.05), social relation skills (β = 0.29; p < 0.05), numeracy skills (β = 0.27; p < 0.05), reading skills (β = 0.25; p < 0.05), writing skills (β = 0.23; p < 0.05), speaking skills (β = 0.21; p < 0.05), conflict resolution and negotiation skills (β = 0.18; p < 0.05). Significant differences existed in the access, acquisition and utilisation of the literacy skills in the two states (t = 2.82, df = 1308, p < 0.05). The FGD also shows that the beneficiaries used skills acquired for their life-improvement activities and they want further improvement opportunities. Access, acquisition and utilisation of basic literacy skills influenced life-improvement skills of rural adult learners. There is the need for improved funding of basic adult literacy and organisers of adult literacy programmes needs to work collaboratively with learners in developing curriculum that meets their basic life-improvement needs as well as increase post literacy activities that will help in sustaining the skills acquired.